2020
DOI: 10.1039/d0cp03609a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the N atom and its position on electron photodetachment of deprotonated indole and azaindole

Abstract: Dipole bound state and its vibrational structure observed in deprotonated 7-azaindole by recording the signal of 7-azaindolyl stable neutral radical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…No fragmentation occurs in the anion excited state nor in the neutral radical. Such behavior was found in deprotonated indole at all energies above the ADE, the excitation of the anion leading to the stable indolyl radical (Figure b) …”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…No fragmentation occurs in the anion excited state nor in the neutral radical. Such behavior was found in deprotonated indole at all energies above the ADE, the excitation of the anion leading to the stable indolyl radical (Figure b) …”
Section: Resultsmentioning
confidence: 64%
“…No fragmentation occurs in the anion excited state nor in the neutral radical. Such behavior was found in deprotonated indole at all energies above the ADE, the excitation of the anion leading to the stable indolyl radical (Figure b) A combination of the two preceding situations: in this case, photodissociation in the anionic excited state occurs together with photodetachment.…”
Section: Resultsmentioning
confidence: 71%
“…20 A previous photodetachment study of indolide revealed a strong threshold peak, which was suggested as possible evidence of a DBS with a low binding energy, but no vibrational Feshbach resonances were observed. 62 When we first conducted the photodetach-ment experiment with a laser scan rate of 0.1 nm/step, we also observed a threshold enhancement but did not observe any DBS features expected as sharp resonances in the otherwise continuous electron signals. Much to our surprise, when we used a 0.005 nm/step scan rate, we discovered extraordinarily sharp resonances in the photodetachment spectrum, as shown in Figure 3.…”
Section: Searching For the Dbs Of Indolide And Resonant Pesmentioning
confidence: 70%
“…In these cases, pure samples of structural isomers were available so-provided no isomerisation occurs upon delivery of ions-the spectra from these isomers can be compared. Such studies have targeted substituted pyridines, [79][80][81][82] azaindoles, 83,84 diazabenzenes, 85,86 indazole and benzimidazole, 87 and diazanaphthalenes, 82 as well as anionic systems: deprotonated azaindoles, 84 nitrophenolate ions, [88][89][90] molecular-iodide clusters, 91 and protonated quinoline and isoquinoline. 54,92 The case of the structural isomers protonated quinoline and isoquinoline is rather straightforward.…”
Section: Isomer Ionsmentioning
confidence: 99%